An Interleaved-Sleeping-Listening scheduler for power saving in mobile stations. (April 2018) - Jayadi, Riyanto; Lai, Yuan-Cheng; Chen, Liang-Chun
Abstract: In mobile networks, the power consumption of a mobile station (MS) can be reduced by entering sleep mode. However, when many connections coexist, the power-saving efficiency is barely satisfactory because the sleep windows of these connections do not overlap and the MS cannot enter sleep mode. Many previous studies tried to shift the sleep windows of some connections where the sleep window is a series of continuous frames. This paper proposes an Interleaved-Sleeping-Listening (ISL) scheduler, which overlaps discrete sleep frames, rather than sleep windows, of multiple connections to obtain a higher number of overlapped sleep frames. The simulation results show that ISL outperforms the previous work, Maximum Unavailability Interval (MUI). When two connections exist and the sleep ratio, the ratio of the sleep frames in a sleep cycle, for each connection is 0.5, ISL improves MUI by 37% on the ratio of unavailability and 15% on the power consumption.